Study about Dielectric Resonator Rectenna for Radio Frequency (RF) Energy Harvesting System - Dwivedi, Vedvyas Jayprakashnarayan; Makwana, Renuka (Theory and Applications of Engineering Research Vol. 8, 2024)
The world is thankful to the Principles, Theories and Practices in the fields of Electromagnetic and RF due to which today we witness the revolution of wireless communication and numerous automation such as satellites, Radar, sensors, automotive, hands-free, blue-tooth, 6G devices and infinitely many more. The research carried out and presented here is a meagre contribution towards upgradation of such technologies useful for the common human beings and much for the environment transformation to eco-friendly nature for future generations to come. Harvesting and re-utilizing the various forms of RF energy has become challenging. Minimizing the wastage of RF energy in the form of electromagnetic waves within the atmosphere is another form of technological challenge. RF energy for specific applications in particular frequency band and conversion into dc-current itself are primary phases of these challenges for most of us in our time. Researches in dielectric resonator rectenna for RF energy harvesting system are quite helpful to resolve such technical challenges. This research presents Star Shaped Dielectric Resonator Antenna (DRA) for receiving RF energy at 2.44 GHz resonant frequency. We have implemented the Star shaped DRA that exhibits 0.8825 W radiation power with reference to 1W incident power wherein the maximum gain is 5.9672 dBi. Also, an appropriate impedance matching circuit along with a rectifier circuit has been designed and presented here for pulsating DC power using capacitive filter to suppress the harmonics.